Hubungan antara derajat dehidrasi dengan penurunan berat badan pada anak diare usia 1 sampai 5 tahun di ruangan kaswari dan poliklinik anak RSUD Wangaya kota Denpasar - William Grandinata Soeseno; I Wayan Bikin Suryawan; Kadek Suarca (DiscoverSys Inc., 2019)
Background: Children with diarrhea occurrences at ages 1 to 5 years had a prevalence of 16,7% in developing countries. Children suffer from diarrhea more than 12 times per year, and this is also the cause of death by 15 – 34 % of all causes of death. Most of the death from diarrhea due to dehydration begin with dehydration symptoms and decreased body weight. Diarrheal disease cannot be underestimated. Comprehensive, holistic and rational handling is required.Methods: This study was observational analytic research with cross sectional study design. This study aimed to investigate the correlation between the degree of dehydration with a weight loss of diarrhea children aged 1 - 5 year. The sample is 55 diarrhea children aged 1 to 5 years with dehydration and without dehydration in Kaswari and Clinic pediatric at Wangaya Hospital Denpasar from May until August 2018. The data was analyzed by Chi-Square testResult: 24 of 30 children aged 1 to 5 years with mild-moderate dehydration diarrhea lose weight (80%), while the other 6 did not lose weight (20%) with p-value = 0,001.Conclusion: There is a relation between degrees of dehydration with weight loss in diarrhea children at Kaswari and clinic pediatric room Wangaya Hospital, Denpasar.